#NoticeUs bipolar disorder: PSA campaign / Siti Noratika Aliasim - Aliasim, Siti Noratika (Faculty of Art and Design, 2020)
The insight that will be highlighted in the #NoticeUs campaign is the importance of noticing people with bipolar disorder.